2018
DOI: 10.1039/c8bm00135a
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of nanointerface curvature and calcium binding in weak polyelectrolyte-coated nanoparticles

Abstract: When engineering nanomaterials for application in biological systems, it is important to understand how multivalent ions, such as calcium, affect the structural and chemical properties of polymer-modified nanoconstructs. In this work, a recently developed molecular theory was employed to study the effect of surface curvature on the calcium-induced collapse of end-tethered weak polyelectrolytes. In particular, we focused on cylindrical and spherical nanoparticles coated with poly(acrylic acid) in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
11
0
1
Order By: Relevance
“…Aptamers are polyelectrolytic in nature with their monomer units (nucleobases) participating in acid-base equilibrium and counterion binding reactions with the surrounding solution environments. Charge regulation and counterion binding in aptamers, or polyelectrolytes in general, are modulated by the metal ions present in the system, which can non-trivially alter their chemical and structural properties [8,9,10,11,12,13]. The presence of metal ions affects the performance of the aptamers as biosensing probes or therapeutics [14,15,16] due to the electrostatic screening of the charges on their surface, which changes their structure and chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers are polyelectrolytic in nature with their monomer units (nucleobases) participating in acid-base equilibrium and counterion binding reactions with the surrounding solution environments. Charge regulation and counterion binding in aptamers, or polyelectrolytes in general, are modulated by the metal ions present in the system, which can non-trivially alter their chemical and structural properties [8,9,10,11,12,13]. The presence of metal ions affects the performance of the aptamers as biosensing probes or therapeutics [14,15,16] due to the electrostatic screening of the charges on their surface, which changes their structure and chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…With ξ > 0, de facto , the pH controls both the ionization degree and the probability of forming c─H‐bonds, their likelihood being a positive concave function of the pH itself, with the limiting value of zero when pH ≪ p K a or pH ≫ p K a . In other terms, c─H‐bond formation may induce deviations from, for instance, the commonly discussed monotonic chain or star expansion as evidenced by Szleifer and coworkers as a consequence of Ca 2+ ‐mediated bridging between carboxylate groups or in presence of hydrophobic forces …”
Section: Resultsmentioning
confidence: 99%
“…As the latter consequence derives from a different behavior of monomers’ chemical potential with respect to the ionization degree from chains without MB interactions, we shall compute the Helmholtz energy of absorbed chains as a function of pH− pK a and exploit it to discuss how ionization impacts on the escape of polymer from an SC. Of relevance for the latter issues, we mention the work by Szleifer and coworkers where the impact on the conformations of multiarmed nanoparticle (NP)‐tethered poly carboxylic acids due to Ca(II) ion coordination as a function of pH and NP curvature radius was studied. The coordination of Ca 2+ by carboxylates (in a 1:2 ratio, respectively) is, de facto , akin to the model discussed above involving the formation of c─H‐bonds, albeit it deviates from the latter in terms of the Gibbs energy change due to species association and for the monotonic increase in the number of Ca 2+ coordination sites upon increasing the pH…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, it was demonstrated that the presence of divalent cations as Ca 2+ and Mg 2+ can lead to the collapse of carboxylic terminated brushes of spherical colloids also provoking their aggregation. 45,46 With the purpose of confirming such hypothesis, the hydrodynamic diameter and surface charge of CaPLiLX sample were evaluated in the presence of 0.05M of divalent cations (Ca 2+ and Mg 2+ ), as depicted in SI, Table S2. An increase of the hydrodynamic diameter of the nanoshells and the consequent decrease in the electrophoretic mobility was observed in the presence of both, Ca 2+ and Mg 2+ , supporting the formation of agglomerates mediated by divalent cations-carboxyl complexes.…”
Section: Proving the Release Mechanism In Sbfmentioning
confidence: 98%